MORPHOGENESIS, STRUCTURAL CHARACTERISTICS AND FORAGE ACCUMULATION OF Megathyrsus maximus BRS ZURI SUBJECTED TO NITROGEN FERTILIZATION - Inacio de Abreu, Mateus Jose; Pereira Paula, Paulo Ricardo; Tavares, Valdir Botega; Cidrini, Iorrano Andrade [UNESP]; Nunes, Henrique de Oliveira; Junior Custodio Emiliano, Welton; Souza, Willian Luiz de [UNESP]; Coelho, Rigles Maia; Neiva Junior, Arnaldo Prata; Paiva Tomaz, Carlos Eduardo de (Inst Zootecnia, 2020)
Nitrogen fertilization permits to increase the carrying capacity of pastures; however, the use of high doses can have negative effects on the growth of forage grasses. Therefore, the aim of this study was to evaluate the influence of increasing nitrogen doses on the morphogenic and structural characteristics, biomass accumulation, and nitrogen conversion and recovery efficiencies of Megathyrsus maximus cv. BRS Zuri. Five nitrogen doses (0, 200, 400, 600 and 800 kg of nitrogen/ha) were tested in a randomized block design with four replicates. A quadratic effect was observed for elongation rate, leaf appearance rate, leaf lifetime, and phyllochron. There was an increase in the number of tillers and in the production of dry matter when the plants were submitted to fertilization; however, both the efficiency of nitrogen use and the apparent recovery of nitrogen decreased linearly with increasing nitrogen level. The use of nitrogen fertilizer improved the morphogenic characteristics, except for stalk elongation rate and leaf senescence rate, which remained stable. Nitrogen fertilization accelerates the growth rates of Megathyrsus maximus cv. BRS Zuri. The maximum responses in the morphogenic variables number of live and total leaves per tiller are obtained with doses close to 500 kg/ha, while doses ranging from 600 to 647 kg/ha provide a larger leaf size per tiller, a higher tiller population density, and higher dry matter production. Nitrogen utilization and recovery efficiencies decrease with increasing nitrogen doses.
Keywords: morphogenic characteristics; nitrogen efficiency; nitrogen fertilizer; forage production; nitrogen recovery